Sculpture. (London : Waddington Galleries, 1982)
Laurens, Henri ; Lichtenstein, Roy ; Lüpertz, Markus ; Martin, Kenneth ; Matisse, Henri ; McWilliam, F.E. ; Milow, Keith ; Miro, Joan ; Moore, Henry ; Turnbull, Willem ; Westermann, H.C. ; etc.
Sculpture, Waddington Galleries, London, 29 September - 23 October 1982
boek